Partial left ventriculectomy in a child: 70-month clinical follow up - Souza,Eduardo Coelho de (2003)
We describe the 70- month follow up of a child with idiopathic dilated cardiomyopathy and end-stage congestive heart failure (NYHA III/IV) who underwent partial left ventriculectomy - the Batista operation when he was two and half years old. The clinical follow up was performed in the outpatient clinic by electrocardiography, echocardiography and radionuclide ventriculography to better analyse the left ventricular ejection fraction. The left ventricular diameter increased. Echocardiograms showed enlargement mainly in the systolic left ventricular diameter and slow decrease in fractional shortening (delta D). The child was in class I (NYHA) during the follow-up. His exercise endurance was better than before surgery and hospitalization was not necessary. For these reasons, we believe that this procedure can be considered as a therapeutic option in children with severe dilated cardiomiopathy who are waiting for heart transplantation, as the shortage of donors is a fact.